2015
DOI: 10.1371/journal.pone.0134157
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Neuropeptides, Neurotransmitters, and Their Receptors in Human Keratocytes In Vitro and In Situ

Abstract: Keratocytes, the quiescent cells of the corneal stroma, play a crucial role in corneal wound healing. Neuropeptides and neurotransmitters are usually associated with neuronal signaling, but have recently been shown to be produced also by non-neuronal cells and to be involved in many cellular processes. The aim of this study was to assess the endogenous intracellular and secreted levels of the neuropeptides substance P (SP) and neurokinin A (NKA), and of the neurotransmitters acetylcholine (ACh), catecholamines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…This has also been explored in a different model and activation of keratinocytes expressing channel rhodopsin via blue light can produce action potentials 12. Keratinocytes express a number of receptors and synthesize neuropeptides, neurotransmitters, and autacoids13 and are also involved in localized inflammatory processes. It is to be acknowledged that these cells may have a key role in the pathogenesis of neuropathic pain 14,15.…”
Section: Focus On the Keratinocytementioning
confidence: 99%
“…This has also been explored in a different model and activation of keratinocytes expressing channel rhodopsin via blue light can produce action potentials 12. Keratinocytes express a number of receptors and synthesize neuropeptides, neurotransmitters, and autacoids13 and are also involved in localized inflammatory processes. It is to be acknowledged that these cells may have a key role in the pathogenesis of neuropathic pain 14,15.…”
Section: Focus On the Keratinocytementioning
confidence: 99%
“…We think that the reason behind muscarinic receptors being responsible for transducing the ACh antiapoptotic signal is the fact that the muscarinic receptors are abundantly expressed by keratocytes. In our previous study, 38 we showed that cultured keratocytes express M1, M3, M4, and M5 subtypes of muscarinic receptors (lacking only M2). We also observed that the M3 receptor was most probably responsible for transducing the ACh-enhanced proliferation signal.…”
Section: Discussionmentioning
confidence: 83%
“…38 Donated corneas were scraped with a scalpel in order to remove epithelial and endothelial cells. Next, the central part of the cornea was separated from the peripheral part, and both were minced with a scalpel.…”
Section: Isolation and Culture Of Primary Keratocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Substance P has been implicated in tissue regeneration/repair, having been found in newt forelimb blastemas . Finally, the cutaneous nerves in the cornea may also provide supportive factors for stem cells residing in the limbal stem cell niche …”
Section: Introductionmentioning
confidence: 99%